Bioactive metabolites from endophytes associated with rubiaceous plants from UiTM Puncak Alam biological reserve / Fatimah Bebe Mohamed Hussain - Mohamed Hussain, Fatimah Bebe (Research Innovation Business Unit, 2014)
Plant endophytes are an important and novel resource of natural bioactive compounds. In the past two decades, many valuable bioactive compounds with antimicrobial, cytotoxic and anticancer activities have been successfully discovered from the endophytic microorganisms. In this research, 54 endophytic fungi and 6 endophytic bacteria were isolated from leaves, stems, flowers and roots of the three plants species of Rubiaceae family collected in the biological reserve, UiTM Puncak Alam, Malaysia. The objective of this study is to isolate bioactive metabolites of endophytic microorganisms from Rubiaceae plants. The microorganisms were inoculated and fermented according to a standardized procedure. The fungal cultures were fermented for 14 days, and we assumed that most secondary metabolites were produced in the media. For bacterial cultures, we assume the length of incubation could be of only 3 days. Each culture was extracted using ethyl acetate based on our standard operation procedure. The crude extracts were evaluated for preliminary screening of antimicrobial activity against Staphylococcus aureus ATCC 25923, Enterococcus faecium ATCC 51585, Pseudomonas aeruginosa ATCC 27853, Escherichia coli ATCC 25922 and Candida albicans ATCC 44831, using MTT method. The principle of MTT assays is to measure the colour of the MTT reagent that is converted from yellow tetrazole to purple formazon in living cells. The purple colouring of the wells in the microtiter plate was interpreted as visible growth of the microorganisms and therefore as a lack of activity of the extracted. Conversely, crude extracts for which no purple formazon could be detected were considered as active. Pleasingly, the antimicrobial effects of these crude extracts were slightly lower than standard antibiotics. The minimum inhibitory concentration (MIC) of the crude ethyl acetate extracts ranged from 0.1875 mg/ ml to 1.5 mg.ml. Six extracts were considered as interesting, as they show significant activites on fungal and bacterial strains and compare the metabolomes of a large number of fungi, it is necessary to rely upon an HPLC procedure that would produce consistent results. The analysis of samples according a standard operating procedure (SOP) requires specifications such as sharp and symmetrical peaks, baseline resolution, and quality chromatogram within a short time. The chromatographic conditions were selected so that the majority of the chromatograms would meet the above specifications. The crude extracts were analyzed by high performance liquid chromatography (HPLC) using diode-array detected (DAD) and evaporative light scattering detector (ELSD). DAD was useful to detect UV active analyses and ELSD to detect non-volatile and non-UV active analyses. HPLC fractionation followed by retesting of the fraction led to correlate chromatographic peaks with biological activity. Pure compound was subjected to standard spectrometry analyzes by mass spectrometry (MS), nuclear magnetic resonance (NMR). ultra violet (UV). infra- red (IR) and comparison with available literature. The combination of UV, MS, and NMR data will quickly determine the structure of known compounds and allow dereplication by referring to a specific database. Data of compounds will be presented. The structure of novel compounds will be elucidated by applying a standard combination of 1D and 2D NMR analysis. The impact of microbial biodiversity, the influence of growth conditions on the production of secondary metabolites, the choice of the best approach at the screening step and the challenges faced during the isolation and identification of the active compounds are examined as the critical factors contributing to success in the effort of antibiotic discovery from microbial natural products (Pelaez, 2006). Therefore, endophytic microorganisms from Rubiaceae plants from biological reserve of UiTM at Puncak Alam could become a source of new lead compounds in view of drug discovery. Antimicrobial, antibacterial, antifungal.